Skating on Olympic ice: Working with winter Olympians - Moyle, G. M. (International Journal of Sport and Exercise Psychology, 2015)
Working as a sport psychologist with Olympic athletes requires a clear understanding of a broad range of multifaceted individual, group, situational, and environmental issues, all of which have the ability to impact upon performance. This article provides an overview of some of the common yet vital issues that have been observed to arise when working with Olympic Winter Games athletes and teams; what to expect, how to recognise them when they occur, and why they are important to prepare for in the context of supporting athletes to achieve the best performance they can at an Olympic Games. Aimed at the emerging sport psychology practitioner, discussion of issues such as performing under pressure, dealing with distractions, adjusting to external factors, team culture, and servicing models creates an informal set of "practical guidelines" based upon real-world experiences that can also be applied to other major sporting competitions.